Embodiment in Patients with Bipolar Disorder: A Dynamic Model - Hossein Khadem; Shahriar Shahidi; Fariba Zarani; Leili Panaghi (International Journal of Body, Mind and Culture, 2022)
Background: Bipolar disorder (BD) is usually studied under the static description and biological etiology, and hence the subjective experience of patients is rarely investigated. This study aimed to investigate the dynamic system of patients with BD through their lived experience in general and their embodiment in specific.